2011
DOI: 10.5713/ajas.2011.11109
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Conjugated Linoleic Acid and Its Combination with Flaxseed Oil or Fish Oil on Saturated Fatty Acid and n-3 to n-6 Fatty Acid Ratio in Broiler Chicken Meat

Abstract: This study examined the effect of CLA, flaxseed oil and fish oil and their combination forms on crude fat of liver and fatty acid profiles of liver, breast and thigh meat in broiler chicks. A total of 72, 1-day-old Cobb broilers were assigned to 6 groups, and fed an experimental diet supplemented with 5 different fat sources; conjugated linoleic acid (2% CLA), flaxseed oil (2% FXO), fish oil (2% FHO), CLA and flaxseed oil combination (1:1; 2% CXO), and CLA and fish oil combination (1:1; 2% CHO). Eight birds pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Ciftci et al [ 18 ] reported that the addition of 500 ppm and 1000 ppm cinnamon oil to the broilers’ ration reduced the ratio of ΣSFA but significantly increased the ratio of Σn-3 and Σn-6 fatty acids, without any affect on ΣMUFA in breast meat. Shin et al [ 54 ] reported that addition of conjugated linoleic acid, flaxseed oil or fish oil at a rate of 2% in ration of broiler chickens decreased PUFA while increasing Σn-3 and Σn-6 levels. Sadeghi et al [ 55 ] reported that addition of fish oil, instead of corn, to the ration at a rate of 5% did not affect SFA, MUFA, PUFA, but decreased Σn-6 and increased EPA and Σn-3 levels in breast meat.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ciftci et al [ 18 ] reported that the addition of 500 ppm and 1000 ppm cinnamon oil to the broilers’ ration reduced the ratio of ΣSFA but significantly increased the ratio of Σn-3 and Σn-6 fatty acids, without any affect on ΣMUFA in breast meat. Shin et al [ 54 ] reported that addition of conjugated linoleic acid, flaxseed oil or fish oil at a rate of 2% in ration of broiler chickens decreased PUFA while increasing Σn-3 and Σn-6 levels. Sadeghi et al [ 55 ] reported that addition of fish oil, instead of corn, to the ration at a rate of 5% did not affect SFA, MUFA, PUFA, but decreased Σn-6 and increased EPA and Σn-3 levels in breast meat.…”
Section: Resultsmentioning
confidence: 99%
“…Bolukbasi et al [ 53 ] reported that the addition of 100 mg/kg and 200 mg/kg of thyme oil to the feed lowered the ratio of ΣSFA in comparison to the control group, while the ratio of ΣPUFA increased in line with the dosage. Shin et al [ 54 ] reported that addition of conjugated linoleic acid, linseed oil or fish oil to the ration at a rate of 2% decreased MUFA level in leg meat while increasing PUFA and Σn-3 values in comparison with the control group. Sadeghi et al [ 55 ] reported that addition of fish oil instead of corn at a rate of 5% to the ration at different weeks (2, 3, 4, 5 and 6) increased SFA and Σn-3 in leg meat in 4th week in comparison to control group, reduced Σn-6 ratio but did not change MUFA and PUFA values.…”
Section: Resultsmentioning
confidence: 99%
“…However, some limited studies imply that excessive intake of n-6 relative to n-3 fatty acids was associated with an increased in cardiovascular heart disease or inflammatory diseases ( Simopoulos, 2003 ; Hibbeln et al, 2006 ). Since consuming a higher amount of n-6 fatty acids has been closely associated with negative health impact, attempts have been made to manipulate the fatty acid profile in human diet, using several fat sources ( Huang et al, 1990 ; Shin et al, 2011 ). Dietary n-6 fatty acid ratio, relative to n-3 fatty acid, was recommended to be decreased, for ideal nutritive value in humans ( Gerster, 1998 ); but it was lower in our study, in both the 0.5% MAP and 1.0% MAP groups (8.20 and 6.08, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…There are 2 possible reasons for this phenomenon in the effectiveness of this product: 1) reduction in unsaturated fatty acid and total unsaturated fatty acid using garlic powder and αtocopherol is related to peroxide-scavenging enzyme activity, which could reduce unsaturated fatty acid and total unsaturated fatty acid oxidation and 2) some active components in the garlic powder and α-tocopherol may involve desaturase and elongase activities (Kim et al, 2005;Guo et al, 2006). Thus, in terms of beneficial health-related biological properties, it is evident that increasing unsaturated fatty acid and total unsaturated fatty acid contents through dietary manipulation (garlic powder and α-tocopherol) could hold promise for the health of consumers (Shahidi, 1996;Belury, 2002). An important acid in chicken meat is also eicosapentanoic acid, which is a precursor of eicosanoids (prostaglandins, tromxoxanes, prostacyclins and leukotrienes) and is important for brain function and vision (Dyall and Michael-Titus, 2008).…”
Section: Resultsmentioning
confidence: 99%